Solar Forcing of ENSO on Century Timescales - Paul S. Wilcox; Manfred Mudelsee; Christoph Spötl; R. Lawrence Edwards (Geophysical Research Letters, 2023)
Abstract Understanding how El Niño‐Southern Oscillation (ENSO) responds to natural variability is of key importance for future climate projections under a warming climate. However, there is no clear consensus on what drives ENSO's variability on centennial timescales. Here, we find that the epikarst in southeastern Alaska is effective at filtering ENSO and solar irradiance signals from the Aleutian Low regional climate, which are subsequently recorded in speleothem proxy data. By applying a correlation test, we find that ENSO was significantly influenced by solar irradiance over the past ∼3,500 years. This relationship dissolved after ∼1970 CE, with ENSO now being dominated by anthropogenic forcing. This implies a new ENSO mean state that will need to be incorporated into future climate projections.